UNIVERSITIES AS GENERATOR FOR REGIONAL DEVELOPMENT - Andrey V. Belotserkovsky (Высшее образование в России)
Some systematic challenges for Russian higher education are considered. Several ways of meeting the challenges are proposed in order to turn regional universities into the centers of regional development.